Assessment on Skeleton Preservation Preparation Techniques of Rats - Habir, Haifa Hazwani; Sapaat, Arney (Enhanced Knowledge in Sciences and Technology, 2026)
This study investigates and compares three preservation techniques for small mammal’s skeletons: burial, boiling and chemical to address persistent problems in preparing rat skeletons for teaching and research. Small mammal bones are fragile and easily damaged and existing methods often produce inconsistent levels of cleanliness, discolouration and loss of structural detail, while also lacking clear information on time and cost efficiency. In response to these gaps, this study aimed to determine which preservation techniques are most effective in maintaining the structure of rat skeletons and to identify methods that are both time‑effective and cost‑effective. Nine protocols were tested: three burial variants (direct, in container, on tray), three boiling variants (plain water, enzyme‑based detergent, papain) and three hydrogen peroxide concentrations (3%, 6%, 15%). Each protocol was evaluated for soft‑tissue removal, bone colour, odor, skeletal integrity, processing time and material cost. Boiling with papain at 40–50°C produced the best overall outcome, yielding bright white, fully defleshed bones within 45 minutes at moderate cost while preserving structural detail. Boiling with enzyme‑based detergent was a useful but slower and cheaper alternative. Chemical maceration with 15% hydrogen peroxide gave rapid whitening in three days but at a higher cost and with a greater risk of surface etching whereas burial methods were the cheapest but required 67 days and were more difficult to manage. These finding suggest that boiling with papain is recommended as the most balanced technique for routine preparation of rat skeletons.